Improvıng Students' Mathematıcs Learnıng Outcomes through The Missouri Mathematics Project (MMP) Learning Model With Realistic Mathematics Approaches For Class VII students of SMP YP PGRI 4 Makassar - Nurfaida Tasni Tasni; Andika Saputra; Berna Rena Bua (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2023)
This study aims to describe the improvement of students' mathematics learning outcomes using the Missouri Mathematics Project (MMP) Learning Model with a Realistic Mathematics Approach. The instruments used in this study were the ability test of students' mathematics learning outcomes, student response questionnaires to the Missouri Mathematics Project (MMP) learning model with the Realistic Mathematics Approach, and teacher and student observation guidelines. Data analysis was carried out in two techniques, namely quantitative and qualitative. The data from the observations and questionnaire responses of students were analyzed qualitatively, while the test of students' mathematics learning outcomes was analyzed quantitatively and strengthened by documentation. This study reveals that the Missouri Mathematics Project (MMP) learning model with the Realistic Mathematics approach (PMR) can improve students' mathematics learning outcomes. This condition can be seen in increased learning results, student activities, teacher activities, and student response questionnaires from cycle I to cycle II. The average value obtained in the first cycle is 61.62 from an ideal score of 100 with a completeness of 19.048%, and at the end of the second cycle, it increases to 79.14 from an ideal score of 100 with a completeness of learning outcomes of 85.714%. The standard deviation in the first cycle is 10,462 and the standard deviation in the final cycle or the second cycle is 9,361. Therefore, the Missouri Mathematics Project (MMP) learning model with the Realistic Mathematics Approach is one of the learning models that can improve students' mathematics learning outcomes because it is one of the models that attracts and motivates students to be more active in learning.